PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI KERJA DAN KECERDASAN EMOSI TERHADAP KINERJA GURU (Studi PadaGuru PAUD dan TK di UPT Dinas Pendidikan Kecamatan Sluke) - Kinayah, 12.52.02.0204; Sunarto, sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze that organizational culture moderates the influence of motivation and emotional intelligence on the performance of early childhood and kindergarten teacher at UPT Department of Education District of Sluke .. This study is the population of all teachers who work in early childhood and kindergarten in the Sub-District Education Office UPT Sluke totaling 100 orang.Pengujian instruments include test validity by factor analysis and reliability test with alpha formula cronbach.Tehnik using multiple regression analysis model of moderation Type Quasi. The results showed that; work motivation does not affect the performance of teachers, emotional intelligence does not affect the performance of the teacher, organizational culture does not affect the performance of teachers, strengthen the organizational culture influence on the performance of teachers work motivation, organizational culture does not strengthen or weaken the effect of emotional intelligence on the performance of teachers in early childKeywords: work motivation, emotional intelligence, organizational culture, teacher performance hood and kindergarten Department of Education District of Sluke .. Â